Impact of COVID-19 Pandemic on Patterns of Care and Outcome of Head and Neck Cancer: Real-World Experience From a Tertiary Care Cancer Center in India. (25th February 2022) - Venkatasai, Jeyaanth; John, Christopher; Kondavetti, Satish Srinivas; Appasamy, Mallika; Parasuraman, Lakshminarasimhan; Ambalathandi, Ravichandran; Masilamani, Hemavathi
Abstract : PURPOSE: The COVID-19 pandemic has caused unprecedented health, social, and economic unrest globally, particularly affecting resource-limited low-middle–income countries. The resultant curfew had made the access to and delivery of cancer care services an arduous task. We have reported the patterns of care and 1-year outcome of head and neck squamous cell carcinoma (HNSCC) treatment before and during COVID-19 lockdown at our institution. MATERIALS AND METHODS: Patients who underwent radiation therapy (RT) for nonmetastatic HNSCC between March 1, 2020, and July 31, 2020, were included in the COVID-RT group, and those who were treated between October 1, 2019, and February 29, 2020, were included in the preCOVID-RT group. RESULTS: A total of 25 patients were in the COVID-RT group, and 51 patients were in the preCOVID-RT group. An increase in the incidence of locally advanced cancers across all subsites was observed in the COVID-RT group. There was a steep increase in the median overall RT treatment duration (52 v 44) and median break days during RT (10 v 2) in the COVID-RT group. The median follow-up period of all patients was 18 months. The progression-free survival at 1 year in the COVID-RT group and preCOVID-RT group was 84% and 90%, respectively ( P = .08), and overall survival at 1 year was 86% and 96%, respectively ( P = .06). CONCLUSION: Our study elucidates the adverse impact of the COVID-19 curfew on cancer care and has demonstrated safe delivery of RT for HNSCC without major acute adverse effects. Despite a significant increase in treatment breaks, early outcome data also suggest that 1-year progression-free survival and overall survival are comparable with that of the pre–COVID-19 times; however, longer follow-up is warranted. Abstract :